(3QGFMI YWQIs - (3ChR, ChRLGfs; (3bWGf, CMeO fhQ GdOjfs ([(3GdQjGV(B]s (3GdeSJbHd GdQbejs, 2021)
(3JfGhd gPg GdSdSdI bUU HYV GdUMGHI GdPjf CMqHhG fHqjfG GdcQje (B((3Udi Gddg Ydjg hSde(B) (3efP cGfhG UZGQkG, hYGThG eYg PcQjGJ LejdI, hJYnqdehG GdcKjQ ef CMGOjKg Yf JYGdje OjffG GdMfja, HTcd oeHnqSW hnSdmS jSJghj CWaGdfG GdUZGQ, hojfqej dOjge MH GdeYQaI hGdbQGAIs
(3GdCfHjGA hGdUMGHIs
(3ddCWaGd ef Sf(B7 (3Edi (B10 (3SfhGJs
Keywords: (3GdCfHjGAs